An introduction to the theory of groups - Aleksandrov, P. S. (Pavel Sergeevich), 1896-1982. (Mineola, N.Y. : Dover Publications, 2012)
" This introductory exposition of group theory by an eminent Russian mathematician is particularly suited to undergraduates, developing material of fundamental importance in a clear and rigorous fashion. A wealth of simple examples, primarily geometrical, illustrate the primary concepts. Exercises at the end of each chapter provide additional reinforcement. 1959 edition"--
Originally published: London : Blackie, 1959.
Includes bibliographical references (p. 109) and index.
Keywords: Group theory; MATHEMATICS / Group Theory